The effect of whole sesame seeds on milk chemical composition, fatty acid profile and antioxidant status in goats - Mitsiopoulou, Christina; Sotirakoglou, Kyriaki; Labrou, Nikolaos; Tsiplakou, Eleni (My University, 2021)
Whole sesame seeds (WSS), although rich in linoleic acid, have not been studied for their impact on the milk fatty acid (FA) profile. Twenty-four goats were divided into three homogeneous subgroups. A control (CON) group and treated groups, in which WSS were incorporated in the concentrates of the CON at 5% (WSS5) and 10% (WSS10), respectively, by partial substitution of both soybean meal and corn grain, were evaluated. Significant increases in the milk fat and total solids contents of goats fed the WSS10 diet compared with the CON were found. In the milk of WSS10-fed goats, the proportions of long-chain fatty acids, monounsaturated fatty acids and unsaturated fatty acids (UFAs) were increased, while those of medium-chain fatty acids and saturated fatty acids (SFAs) were decreased compared with those of the CON group. Significant decreases in the proportions of short-chain fatty acids, in the SFA/UFA ratio and in the atherogenicity index value in milk of treated goats were observed. The proportions of C15:0 and C17:0 FAs in the blood plasma of WSS10-fed animals compared with CON-fed animals were reduced significantly. Superoxide dismutase and catalase activities increased significantly in the blood plasma of WSS10-fed goats compared with CON-fed goats. Additionally, in the treated goats, the protein carbonyls (PC) in blood plasma and both PC and malondialdehyde contents in milk declined significantly. A significant enhancement in the total antioxidant capacity [measured by the ferric reducing ability of plasma (FRAP)] in the milk of WSS10-fed goats compared with the CON was found. Similarly, an increase in the FRAP value of milk of WSS5-fed goats compared with CON-fed goats was observed. In conclusion, the highest inclusion level of WSS (WSS10) in goat diets improves the FA profile and the oxidative stability of milk and improves the organism's antioxidant status.
Keywords: Sesame seeds; Milk fatty acid; Goats